Room-Temperature-Sputtered Nanocrystalline Nickel Oxide as Hole Transport Layer for p-i-n Perovskite Solar Cells - Schwingenschlögl, Udo; De Wolf, Stefaan; Laquai, Frédéric; Aydin, Erkan; Troughton, Joel; Neophytou, Marios; Baran, Derya; De Bastiani, Michele; Ugur, Esma; Sajjad, Muhammad; Alzahrani, Areej (My University, 2018)
Nickel oxide (NiO x ) is a promising hole transport layer (HTL) for perovskite solar cells (PSCs), as it combines good chemical stability, high broadband optical transparency, and a high work function. Excellent power conversion efficiencies (PCEs) have already been reported using solution-processed NiO x . However, solution-based techniques usually require high-temperature postannealing to achieve the required HTL properties of NiO x , which jeopardizes its use for many applications, such as monolithic tandem solar cells. To resolve this issue, we developed room-temperature-sputtered NiO x and demonstrated p-i-n PSCs with 17.6% PCE (with negligible hysteresis), which are comparable to the best PSCs using sputtered and annealed NiO x without heteroatom doping. Through detailed characterization and density functional theory (DFT) analysis, we explored the electrical and optical properties of the obtained NiO x films and find that they are strongly linked with the specific defect chemistry of this material. Finally, in view of its use in perovskite/silicon tandem solar cells, we find that direct sputtering on random-pyramid textured silicon wafers results in highly conformal NiO x films.
Keywords: Plastic optical fibers; Microstructured polymer; Bragg gratings